PROBLEMS OF EFFECTIVE USE OF ELECTRICAL ENERGY IN AGRICULTURE AND WATER MANAGEMENT - (PhD) Yulchiev Mash'albek Erkinovich; Poziljonova Dilbaroy Hakimjon qizi; Raxmatullayev Shamsiddin Hakimboy o ‘g ‘li (Лучшие интеллектуальные исследования, 2024)
Abstract: Electricity is one of the most consumed resources and the demand is increasing day by day. As the demand for global energy resources increases day by day, it creates a series of problems in the field of energy. These problems are in industrial production, in productions, as a result of economic activities, the economy and people's lifestyles were brought to a bad state, therefore, as a result of research, a new technological system was developed and started to be introduced. Agrovoltaics is a new and effective method in agriculture.